Anesthesia for Open Radical Retropubic Prostatectomy: A Comparison between Combined Spinal Epidural Anesthesia and Combined General Epidural Anesthesia. (14th May 2019) - Kofler, O.; Prueckner, S.; Weninger, E.; Tomasi, R.; Karl, A.; Niedermayer, S.; Jovanovic, A.; Müller, H. H.; Stief, C.; Zwissler, B.; von Dossow, V.
Abstract : Background . Several anesthesiologic regimens can be used for open radical retropubic prostatectomy. The aim of this retrospective analysis was to compare the combined general epidural anesthesia and the combined spinal epidural anesthesia with regard to availability, efficacy, side effects, and perioperative time consumption in a high-volume center. Methods . A retrospective analysis was performed by querying the electronic medical records of 1207 consecutive patients from the database of our online documentation software. All patients underwent open radical retropubic prostatectomy from 01/2008 to 08/2011 and met the study criteria. Linear and multivariate regression analyses were performed to identify differences in parameters such as time consumption in the operating unit, hemodynamic parameters, volume replacement, and catecholamine therapy. Results . 698 (57.8%) patients have been undergoing open radical retropubic prostatectomy under combined spinal epidural anesthesia and 509 (42.2%) patients by combined general epidural anesthesia. Operating unit (p <0.0001) and post-anesthesia care unit stay (p <0.0001) as well as total hospital stay (p <0.0001) were significantly shorter in the combined spinal epidural anesthesia group. In addition, this group had reduced intraoperative volume need (p <0.0001) as well as lower need of catecholamines (p <0.0001). Conclusions . This retrospective study suggests that the combined spinal epidural anesthesia seems to be a suitable and efficient anesthesia technique for patients undergoing open radical retropubic prostatectomy. This specific approach reduces time in the operation unit and length of hospital stay.